Measurement of circulating transcript levels (NETest) to detect disease recurrence and improve follow‐up after curative surgical resection of well‐differentiated pancreatic neuroendocrine tumors. Issue 1 (16th August 2018) - Genç, Cansu G.; Jilesen, Anneke P.J.; Nieveen van Dijkum, Els J.M.; Klümpen, Heinz‐Josef; van Eijck, Casper H.J.; Drozdov, Ignat; Malczewska, Anna; Kidd, Mark; Modlin, Irvin
Abstract : Background: Recurrence of pancreatic neuroendocrine tumors (pNET) after surgery is common. Strategies to detect recurrence have limitations. We investigated the role of clinical criteria and the multigene polymerase chain reaction–based NETest during post‐operative follow‐up of pNET. Methods: We studied 3 groups of resections: R0 with no recurrence (n = 11), R0 with recurrence (n = 12), and R1 with no recurrence (n = 12). NETest levels (>40%) were compared with chromogranin A (CgA) and clinicopathological criteria (CC; grade, lymph node metastases, size). Nonparametric, receiver operating characteristics, logistic regression, and predictive feature importance analyses were performed. Results: NETest was higher in R0 with recurrence (56 ± 8%) compared with R1 with no recurrence (39 ± 6%) and R0 with no recurrence (28 ± 6%, P < .005). NETest positively correlated with recurrence (area under the curve: 0.82), CgA was not (area under the curve: 0.51 ± 0.09). Multiple regression analysis defined factor impact as highest for NETest ( P < .005) versus CC ( P < .03) and CgA ( P = .23). NETest gave false positive or negative recurrence in 18% using a 40% cutoff. Logistic regression modeling of CC was 83% accurate; it was 91% when the NETest was included. Combining CC and NETest was approximately 2× more effective than individual CC alone (increase in R 2 value from 43% to 80%). Conclusions: A multigene blood test facilitates effective identification of pNET recurrence, prediction of disease relapse, and outperforms CgA.